LIFE AND WORK OF THE MUNAVVARQORI ABDURASHIDKHANOV - Ravshanova Umida Kamolovna (Galaxy International Interdisciplinary Research Journal, 2021)
The last 130 years of the history of the Uzbek people have passed in the composition of the “White” and “red” Kingdoms. The Tsar and the representatives of the Soviet countries, who set themselves the goal of looting the material and cultural wealth of the Uzbek land, permanently destroyed the people who wanted to see it free and free, who worked on this path. As a result of such a terrible policy, generations did not know for many years the great surrogates that reached the twentieth century from the Uzbek people. The name of those who carried a beacon from burnt, heartbroken blood will never forget. No matter how many politicians condemn such people, they themselves will remain before the land, history and times. After all, both hometown and history preserve the selfless people in their hearts. One of such signs, which our people wanted and passed on from generation to generation, was writer, poet and pedagogue, public figure Munavvarqori Abdurashidkhanov. In this article, opinions and comments are made about the life and work of the Munavvarqori Abdurashidkhanov.